Bash quick reference - Robbins, Arnold (O'Reilly, 2006)
In this quick reference, you'll find everything you need to know about the bash shell. Whether you print it out or read it on the screen, this PDF gives you the answers to the annoying questions that always come up when you're writing shell scripts: What characters do you need to quote? How do you get variable substitution to do exactly what you want? How do you use arrays? It's also helpful for interactive use. If you're a Unix user or programmer, or if you're using bash on Windows, you'll find this quick reference indispensable.
Includes index. - Print version record
Keywords: UNIX (Computer file); UNIX Shells; COMPUTERS; Operating Systems; DOS; COMPUTERS; Operating Systems; Macintosh; COMPUTERS; Operating Systems; Windows Server & NT; COMPUTERS; Operating Systems; Windows Workstation; COMPUTERS; System Administration; Windows Administration